The Development of Exploding Box Learning Media in Sex Education for Elementary School Students - Apriliyanti, Lala Fira Dwi; Lestari, Indah Dwi; Maulani, Magfiroh Izza (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
Along with the development of the era, there are many social problems that arise in Indonesia, one of them is sexual harassment by sex criminals. Children are often victims of sexual abuse. One way that can be done to prevent the occurrence of this case is by providing early sex education to children, assisted by the Exploding Box learning media. In the Exploding Box, there is some basic knowledge about sex, so it is hoped that it can make things easier for parents and educators to explain sex education to their children and students. The purpose of this study is to describe the development steps and determine the feasibility of the Exploding Box as a medium for sex education for primary school-aged children. The method used is research and development (R&D). The results obtained are that the child knows some of the basics of sex education but does not know that the knowledge that they have is actually sex education, while parents experience difficulty in explaining sex education to children because they feel taboo if they have to explain directly, therefore educational media that can explain it are needed. Sex education to children with an attractive but not lost goal. Thus, the exploding box can be developed into a sex education medium for elementary school children with material adapted to sex education. In its development, the material was adapted to a grid, which was then validated and refined to obtain a proper sex education media.